Wind Energy Exploitation in Urban Environment TUrbWind 2017 Colloquium (Green Energy and Technology, 2018)
This book presents numerical and experimental research in the field of wind energy exploitation in urban environments. It comprises a selection of the best papers from the international colloquium "Research and Innovation on Wind Energy Exploitation in Urban Environment" (TUrbWind), held in Riva del Garda, Italy in June 2017. The book includes contributions from different research fields in urban wind resources, wind energy conversion systems, and urban integration, mainly focusing on the following topics: · concepts for urban and open landscape micro wind turbines, · integration of micro wind turbines in existing structures, · built-environment and high-turbulence sites' impacts on urban wind turbines, · measuring and modeling wind resource in built environments, · rotor performance and wake features of micro wind turbines. It is a valuable resource for researchers and practitioners interested in the integration of wind energy systems and turbines in urban areas.